Teratogenic of 2,3,7,8-Tetrachlorodibenzo-P-Dioxin (TCDD) on Eye Diameters and Body Weight in Chicken Embryo - Firdaus, Muhammad Aviv; Pratiwi, Herlina; Setianingrum, Ani; Airlangga, Gegana Wimaldy (Universitas Airlangga, 2021)
2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a chemical compound resulting from the burning effect that is very dangerous for humans, plants, or animals which can cause skin damage, immunotoxic, hepatotoxic, carcinogenic, teratogenic, effects on reproduction, growth processes, neurobehavioral, and endocrine effects that are specific In addition, this compound can also reduce embryo weight and increase embryo mortality. This study aimed to determine the teratogenic of TCDD administration on eye diameters and body weight of chicken embryo. In this study there were 2 treatment groups, i.e: 1) P1 as a normal group without the addition of TCDD, and 2) P2 as a group with the addition of TCDD of 5 ng / egg with dissolved in 5 µL corn oil. The treatment was carried out for 7 days. The measurement data of eye diameters and body weight of chicken embryo were analyzed by the unpaired sample T test. The analysis showed that the teratogenic of TCDD had a significant effect on eye diameters and body weight of chicken embryos, where the teratogenic of TCDD caused a decrease in eye diameters and body weight loss in chicken embryos.